Microencapsulation of omega-3 fatty acids: What it is, how it’s made, and challenges in food technology - Sri Haryani Anwar (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2011)
Fatty acids with double bonds beyond the ninth carbon from the carboxyl end are classified as essential for human health, including omega-3 fatty acids: eicosapentaenoic acid (EPA) and docosahexanoic acid (DHA). The main sources of omega-3 fatty acids are fatty fish species such as herring, mackerel, sardine and salmon. Oils from the marine algae Cryptecondium conchii are mainly rich in DHA only, while fish oil contains both EPA DHA. Why is it important to microencapsulate EPA DHA? Because these fatty acids cannot be synthesized by the human body but have to be obtained through nutrition uptake. The beneficial effects of these fatty acids including lowering cholesterol, decreasing the risk of arrhythmia, lowering the blood pressure, preventing diabetes in pregnancy, and positive effects on joints (relief of arthritis). EPA and DHA also play an important role in early infant nutrition and the imbalance of these fatty acids is believed to cause a variety of diseases. Because of their sensitivity to oxidation, these fatty acids need to be stabilized to protect them from oxidation. In food application, their interaction with other food ingredients needs to be prevented. Attempts to prevent oxidation to allow omega-3 fatty acids to fulfill their functions are not trouble-free. Fish oils in their natural state have a taste and smell that make them less attractive to consumers. Processing technology for masking the smell and taste of fish oil in food faces great challenges. Therefore, to address the problems concerning the susceptibility of fish oil to oxidation and its unpleasant smell, microencapsulation, where the oil is packaged within coating materials, may be used to replace bulk oils. This paper discusses great challenges faced by the scientists to microencapsulate omega 3 fatty acids from fish oil after introducing concise information related to microencapsulation and its advance techniques. As the demand of functional food containing omega-3 is continuously growing, overcoming those challenges mean solving one problem in providing healthy food for the world